Beyond Euro‐Americancentric Forms of Racism and Anti‐racism. Issue 3 (12th July 2022) - Modood, Tariq; Sealy, Thomas
Abstract: Following the killing of George Floyd by the police in the US in May 2020, a new anti‐racism has erupted across the world. While this anti‐racism is squarely focussed on dismantling anti‐black racism, scholarship—especially in western Europe—has for some decades now been emphasising racisms : Anti‐South Asian racism, Islamophobia and Sinophobia in Britain, anti‐Arab racism in France and anti‐Turk and anti‐migrant racisms in Germany, and so on. These various forms of racism do not just refer to the use of biological features, but also perceived cultural features in the way that particular groups are constructed and rendered as 'other'—cultural racisms. Yet, this scholarship is deeply Euro‐Americancentric as it barely acknowledges racisms outside the West and least of all racisms that do not involve white perpetrators. This special issue considers a number of such racisms and anti‐racisms in Asia and the Middle East.